GAYA BELAJAR PESERTA DIDIK BERPRESTASI AKADEMIK KELAS V SD NEGERI 1 NANGA PINOH - Simaremare, Milawati ,; Mardiana, Mardiana; Apsari, Nurul (STKIP Melawi, 2023)
This study aims to describe the learning styles used by students with academic achievements at class V students of SDN 1 Nanga Pinoh. The subjects in this study were students with academic achievements who had ranks 1, 2 and 3. This research is a qualitative research. The data collecting process is held through observations, interviews and documentations. Data analysis in this study used the Milles and Huberman data analysis techniques. Data analysis techniques are carried out by collecting, reducing, displaying, and drawing conclusions. Data validity test was carried out by source triangulation. The results of this study indicate that the learning styles of students with academic achievements at class V of SDN 1 Nanga Pinoh are a combination of visual, auditory, and kinesthetic learning styles so that the tendency of the types of learning styles of students with academic achievements is different. So that the calculation results show that 80% of students with academic achievement have an auditory learning style, 53.33% of students with a kinesthetic learning style, and 40% of students with a visual learning style and there are factors that influence the learning styles of students with academic achievement, namely physical/physical factors, emotional/psychological factors, social factors and environmental factors.